Intermediation and Resale in Networks - Manea, Mihai (Journal of Political Economy, 2018)
I study intermediation via sequential bilateral bargaining in markets with a network structure. A partition of the network into layers captures intermediation power. Competition governs trade within layers, and hold-ups generate intermediation rents in transactions between layers. Each trader’s intermediation power reflects the competition among intermediation chains as measured by the number of layers separating the trader from buyers. Trade does not maximize welfare or minimize intermediation. The interplay between competition and hold-ups determines the level of inefficiency. Eliminating middlemen or transferring intermediation costs downstream increases seller profits. Downstream and upstream competition respond oppositely to either horizontal or vertical integration.